2015
DOI: 10.5455/ijmsph.2015.060920141
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and etiological profile of thrombocytopenia in adults: A tertiary-care hospital-based cross-sectional study

Abstract: Background: The etiologies of thrombocytopenia are diverse. Various studies on thrombocytopenia are done in the past have related to specific etiologies. Objectives: This study attempts to determine the common etiologies of thrombocytopenia in adult patients admitted to Civil Hospital, Ahmedabad. Material and Methods: A cross-sectional study was carried out at Civil Hospital, Ahmedabad. Patients with thrombocytopenia more than 18 years of age at admission between 1 October and 31 October 2013 were followed up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…Male were commonly suffering from fever, this may be due to their easy exposure to mosquito because of their outdoor activities. Our finding of occurrence of fever with thrombocytopenia more in male than female is similar to study done by Bhalara SK Shah et al [4] in 2015. In our study…”
Section: Discussionsupporting
confidence: 92%
“…Male were commonly suffering from fever, this may be due to their easy exposure to mosquito because of their outdoor activities. Our finding of occurrence of fever with thrombocytopenia more in male than female is similar to study done by Bhalara SK Shah et al [4] in 2015. In our study…”
Section: Discussionsupporting
confidence: 92%
“…9 Another study done by Bhalara, showed dengue (60.8%) as the main aetiology. 10 In present study, viral infections were the commonest cause due to the higher prevalence of these infections during the rainy season. This difference could have been due to seasonal and regional variation.…”
Section: Discussionmentioning
confidence: 59%
“…In another study by Bhalra, dengue was found as the main aetiology (60.8%). 15 In this study dengue was found only in (3.35%) cases in pyrexia group.…”
Section: Discussionmentioning
confidence: 47%